Cost-effectiveness analysis of PD-1 inhibitors combined with chemotherapy as first-line therapy for advanced esophageal squamous-cell carcinoma in China - Liu, Shixian; Dou, Lei; Li, Shunping (Frontiers in Pharmacology, 2023)
Objective: This study was aimed to investigate the cost-effectiveness of all available programmed death 1 (PD-1) inhibitors combined with chemotherapy in the first-line treatment of advanced esophageal squamous-cell carcinoma (ESCC) from the Chinese healthcare system perspective. Methods: A partitioned survival model with a 3-week cycle and a 10-year time horizon was constructed based on a published network meta-analysis. The survival data and utility values were derived from clinical trials, and the direct medical costs were collected from public drug bidding database and published literature. Total costs, quality-adjusted life-years (QALYs) and incremental cost-effectiveness ratios (ICERs) were calculated. Scenario, one-way and probabilistic sensitivity analyses were performed to assess the uncertainty around model parameters. Results: Compared with mono-chemotherapy, domestic PD-1 inhibitors, toripalimab, camrelizumab and sintilimab, combined with chemotherapy were cost-saving options with higher QALYs at lower costs. Toripalimab plus chemotherapy provided the highest QALYs of 1.13 with the lowest cost of 7,595.69, compared to other competing alternatives. The cost-effectiveness acceptability curve showed that toripalimab plus chemotherapy was the optimal option in approximately 98.96% and 84.32% of the iterations, respectively, when the willingness-to-pay thresholds was one and three times per capita gross domestic product (12783.73 and 38,351.20) in 2021. Conclusion: Toripalimab plus chemotherapy represented the most cost-effective option as the first-line therapy for advanced ESCC patients in China.